1973
DOI: 10.1508/cytologia.38.497
|View full text |Cite
|
Sign up to set email alerts
|

Synaptonemal Complex of Haploid Maize

Abstract: Since the application of electron microscopy in the study of chromosomes of eukaryotes, results have not been as expected. For instance, electron microscope has failed to reveal the structural characteristics of the chromosomes related to these that were observed with light microscope, and electron microscope has not substantiated the conclusions generalized with cytogenetic researches. Further more, there is still no unified concept of the unit structure of chromosomes at fine structure level. However, in 195… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…These concepts have been supported by ultrastructural studies, documenting the presence of synaptonemal complexes in haploids of e.g. maize (27) and Petunia and Antirrhinum (24). In monohaploids of barley up to 60% of the complement was combined with a synaptonemal complex (5).…”
Section: Introductionmentioning
confidence: 88%
“…These concepts have been supported by ultrastructural studies, documenting the presence of synaptonemal complexes in haploids of e.g. maize (27) and Petunia and Antirrhinum (24). In monohaploids of barley up to 60% of the complement was combined with a synaptonemal complex (5).…”
Section: Introductionmentioning
confidence: 88%
“…Whereas random bivalent formation has been suggested by Govindaswami & Pachytene observations by light microscopy revealed occasional interchromosomal and intrachromosomal pairing in monoploids of rice (Chu, 1967), tomato (Ecochard et al, 1969), maize (Ting, 1966;Ford, 1970;Weber & Alexander, 1972) and barley (Sadasivaiah & Kasha, 1971, 1973. These findings were corroborated by studies based on threedimensional reconstruction of pachytene nuclei by electron microscopy that revealed the existence of synaptonemal complexes (SCs) in monoploids of tomato (Menzel & Price, 1966), maize (Ting, 1973), petunias and snapdragons (Sen, 1970) and barley (Gillies, 1974). However, with this methodology only a limited number of nuclei can be analysed, which prevents a quantitative study of SC formation.…”
Section: Introductionmentioning
confidence: 91%
“…Several cases are known however, where extensive chromosome pairing with synaptonemai complexes occurs between apparently non-homologous chromosome segments. Synaptonemal complexes are readily observed in haploid maize (46,47), barley (8), Petunia and Antirrhiuum (36), and tomato 08). In haploid barley, up to 60% of the lateral component length is paired into synaptonemal complexes, which are morphologically indistinguishable from complexes between homologous chromosomes (8).…”
Section: Specificity Of Chromosome Pairingmentioning
confidence: 99%
“…Studies on chromosome pairing in haploid organisms (5,8,36,47) have demonstrated that extensive, presumably non-homologous, chromosome pairing can occur, and in barley may include up to 60% of the lateral components. Synaptonemal complexes between non-homologous chromosomes are morphologically indistinguishable from complexes between homologous chromosomes (8).…”
Section: Introductionmentioning
confidence: 99%